Charles Stuart Aubrey Abbott, Baron Tenterden, correspondence - Tenterden, Charles Stuart Aubrey Abbott, Baron, 1834-1882.
Six letters of introduction written by Tenterden to British officials on behalf of James Brooks, U.S. representative from New York.
British diplomat serving in Washington, D.C.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Brooks, James, -- 1810-1873.; Diplomatic and consular service, British -- United States; New York (State) -- Politics and government -- 1865-1950.; Diplomats -- Great Britain